2020
DOI: 10.1634/theoncologist.2019-0796
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophic Lichen Planus with Histological Features of Squamous Cell Carcinoma Associated with Immune Checkpoint Blockade Therapy

Abstract: Immune checkpoint blockade (ICB) is highly effective for the treatment of metastatic cancers, but its side effects are incompletely understood. The objective of this article is to highlight hypertrophic lichen planus (HLP) with histological features diagnosed as squamous cell carcinoma (SCC), which is a potential cutaneous reaction to ICB. Two patients (75 and 69 years) presented with lesions diagnosed as SCC on biopsy, which developed after 3-9 months on ICB therapy. Biopsies demonstrated endophytic, atypical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…There are case reports in the literature describing similar scenarios of lichen planus misdiagnosed as squamous cell carcinoma after skin biopsy as there are overlapping clinical, and histopathological features between the two entities [12][13][14][15]. Similar to other case reports, lesions appeared after several months of PD-1/PD-L1 blockade for our patients [14,35,36].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…There are case reports in the literature describing similar scenarios of lichen planus misdiagnosed as squamous cell carcinoma after skin biopsy as there are overlapping clinical, and histopathological features between the two entities [12][13][14][15]. Similar to other case reports, lesions appeared after several months of PD-1/PD-L1 blockade for our patients [14,35,36].…”
Section: Discussionsupporting
confidence: 80%
“…Skin irAEs remain poorly characterized and the spectrum of reactions remains to be fully elucidated. There are several case reports in the literature describing patients on ICIs who were initially diagnosed with squamous cell carcinomas, but further review revealed it was a lichenoid reaction due to PD-L1/PD-1 checkpoint inhibition [12][13][14][15]. Here, we report on two cases of ICI-induced dermatitis eruptions which were initially diagnosed with squamous cell carcinoma, but the clinical course and further pathological clarification were more consistent with a skin irAE.…”
Section: Introductionmentioning
confidence: 74%
“…Twenty-five articles that discussed 123 lichenoid cirAEs were identified following treatment with immunotherapy . One hundred six lichenoid eruptions (86.2%) developed following PD-1/PD-L1 inhibitor monotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Nail involvement with dystrophy, ridging, and hyperkeratosis have also been reported. Several other clinical types of lichen planus have been described in case reports and case series, including erosive and hypertrophic variants, bullous lichen planus pemphigoids, and inverse lichen planus [ 51 ].…”
Section: Cutaneous Immune-related Adverse Eventsmentioning
confidence: 99%
“…Unlike typical lichen planus, apoptotic keratinocytes—associated with variable parakeratosis, necrosis, epidermal spongiosis, and eosinophils—may be seen. Recent reports also describe a clinical type of hypertrophic lichen planus with squamous cell carcinoma-like histology [ 51 ].…”
Section: Cutaneous Immune-related Adverse Eventsmentioning
confidence: 99%